Landeskunde Aspects in the Textbook Beste Freunde A1.1: Kursbuch - Tiara Rahma Dhania; Santiah Santiah; Melky Ayu Wijayanti (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2026)
The purpose of this study is to analyse the aspects of Landeskunde found in the textbook Beste Freunde A1.1: Kursbuch. This study uses a qualitative descriptive method with content analysis techniques. The data were obtained from audio material, dialogues, images, short descriptive texts, and tables that contain elements of Landeskunde. The analysis referred to the Inhalt-Landeskunde proposed by Krumm, which consists of 8 aspects of Landeskunde. The results show that 41 aspects of Landeskunde in 32 data, namely 21 aspects of Der Alltag im Lehrwerk, 10 aspects of Die Meschen, die im Lehrwerk vorkommen, then 6 aspects of Geographie und Wirtschaftsleben, then 3 aspects of Literatur, and one aspect of Kultur. In addition, there are several aspects that are not found in this textbook, namely the aspects of Darstellung des eigenen Landes, Die Gesellschaft (politische, wirtschaftliche und gesellschaftliche Verhältnisse), and also Geschichte. In conclusion, the textbook can introduce basic aspects of Landeskunde integrated into beginner-level German language learning materials.